Characteristic Evolution of Inter-Industry Liquidity Spillover Effect in China's Stock Market -- An Analysis based on Complex Network - Li, Siwen; Zhao, Yiquan; Feng, Haoyuan; Lu, Yaqiang; Dai, Xueliang (BCP Business & Management, 2022)
In recent years, the liquidity risk of China's stock market occurs frequently and spreads among different industries. The study of liquidity spillover is of great significance to prevent systematic financial risk. Based on the industry transaction data of China's stock market from 2011 to 2021, this paper calculates the market liquidity of different industry indexes, constructs Granger causality network in stages, and discusses the heterogeneity of the spillover effect of liquidity at the industry level in different economic stages. It is found that there is a significant liquidity spillover effect among industries; Compared with the stage of high leverage and loose monetary policy, under the background of stable macro leverage ratio and stable monetary policy, the liquidity spillover effect among industries will be weakened; The impact of liquidity has gradually changed from the spillover impact of traditional industries to the spillover impact of emerging industries.